Lung toxicity profile of inhaled copper-nickel welding fume in A/J mice. (24th August 2022) - Zeidler-Erdely, Patti C.; Erdely, Aaron; Kodali, Vamsi; Andrews, Ronnee; Antonini, James; Trainor-DeArmitt, Taylor; Salmen, Rebecca; Battelli, Lori; Grose, Lindsay; Kashon, Michael; Service, Samantha; McKinney, Walter; et al.
Abstract: Objective: Stainless steel welding creates fumes rich in carcinogenic metals such as chromium (Cr). Welding consumables devoid of Cr are being produced in an attempt to limit worker exposures to toxic and carcinogenic metals. The study objective was to characterize a copper-nickel (Cu-Ni) fume generated using gas metal arc welding (GMAW) and determine the pulmonary deposition and toxicity of the fume in mice exposed by inhalation. Materials and Methods: Male A/J mice (6–8 weeks of age) were exposed to air or Cu-Ni welding fumes for 2 (low deposition) or 4 (high deposition) hours/day for 10 days. Mice were sacrificed, and bronchoalveolar lavage (BAL), macrophage function, and histopathological analyses were performed at different timepoints post-exposure to evaluate resolution. Results and Discussion: Characterization of the fume indicated that most of the particles were between 0.1 and 1 µm in diameter, with a mass median aerodynamic diameter of 0.43 µm. Metal content of the fume was Cu (∼76%) and Ni (∼12%). Post-exposure, BAL macrophages had a reduced ability to phagocytose E. coli, and lung cytotoxicity was evident and significant (>12%–19% fold change). Loss of body weight was also significant at the early timepoints. Lung inflammation, the predominant finding identified by histopathology, was observed as a subacute response early that progressively resolved by 28 days with only macrophage aggregates remaining late (84 days). Conclusions: Overall, there was high acute lung toxicity with a resolution of the response in mice which suggests that the Cu-Ni fume may not be ideal for reducing toxic and inflammatory lung effects.